Participation for Sustainability in Adult Literacy and Skills Acquisition Centers - Mohammed, Yusuf; Mokhtar, Mahani (International Journal of Psychosocial Rehabilitation, 2020)
The success of every society depends on the quality and quantity of education of its citizens. Literacy centers were established mainly to empower adult members with the right type of literacy and functional education needed for their improvement. This review attempts to highlight the mechanisms of participation for sustainable adult literacy and skill acquisition programs. This review considered the concept of adult literacy and skill acquisition participation mechanisms. Relevant literature was identified and scrutinized. These mechanisms are not entirely new but are often neglected and improperly utilized, mainly because the practitioners are less motivated to care about them. Results indicate that the rate of adult participation in many countries across the globe seems not to be hopeful, especially in the developing countries. The concept of participation, type, role, and factors that inhibit/facilitate sustainability in adult literacy and skills acquisition programs were discussed. This review pointed out that barriers such as situational, institutional, and dispositional are some of the principal inhibitors to participation in adult education. Lastly, the connection between participation and sustainability was deliberated. This was followed by suggestions on how to improve participation for the sustainability of adult literacy program(s). However, additional studies are required on the subject of adult literacy, because the topic is suffering neglect in educational research.